Erythrocytes from patients with ST-elevation myocardial infarction induce cardioprotection via the purinergic P2Y13 receptor and nitric oxide signalling. (3rd October 2022) - Jiao, T; Mahdi, A; Tengbom, J; Collado, A; Jurga, J; Saleh, N; Verouhis, D; Bohm, F; Zhou, Z; Yang, J; Pernow, J
Abstract: Background: Red blood cells (RBC) are suggested to act as important mediators in the regulation of cardiovascular function by exporting nitric oxide (NO) bioactivity and ATP under hypoxic/ischemic conditions. In addition, RBCs are known to protect from ischemia-reperfusion injury via the export of NO bioactivity in experimental settings. However, it remains unknown if such beneficial effects of RBCs are protective in patients with acute myocardial infarction. Purpose: To investigate whether RBCs from patients with ST-elevation myocardial infarction (STEMI) protect against myocardial ischemia-reperfusion injury and whether such effect involves activation of purinergic and NO signalling in the RBCs. Methods: RBCs were collected from patients with STEMI undergoing primary percutaneous coronary intervention and age- and gender-matched healthy controls. The RBCs were administered into the coronary circulation of isolated Langendorff-perfused rat hearts at the onset of global ischemia for 25 min followed by reperfusion of 60 min. Recovery of left ventricular developed pressure (LVDP) during reperfusion and infarct size were determined. All animal experiments and procedures were performed according to the guidelines by the U.S National Institutes of Health (NIH publication no 85–23, revised 1996). The present study was performed following The Code of Ethics of the World Medical Association outlined in the Declaration of Helsinki of 1975 and revised in 1983 for experiments that involve human subjects. Results: Administration of RBCs from STEMI patients improved recovery of LVDP and reduced infarct size in hearts subjected to ischemia-reperfusion in comparison with RBCs from healthy controls (Figure 1A, B). Pre-incubation of the RBCs with the NO synthase (NOS) inhibitor L-NAME (Figure 1C, D) and the inhibitor of the NO receptor soluble guanylyl cyclase (sGC) ODQ abolished the cardioprotective effect of RBCs from STEMI patients. The cardioprotective effect was also attenuated by inhibition of cardiac cGMP-dependent protein kinase (PKG). Further, the purinergic P2Y13 receptor antagonist MRS2211 (Figure 1E, F), but not the P1 receptor antagonist 8PT applied to RBCs, attenuated the cardioprotection induced by RBCs from STEMI patients. Moreover, administration of RBCs from healthy subjects pre-incubated with a cell permeable ATP analogue improved post-ischemic recovery of LVDP and reduced infarct size. This cardioprotective effect was abolished by co-incubation of the RBCs with ODQ (Figure 2) and MRS2211. Conclusion: Our findings demonstrate a novel function of RBCs in patients with STEMI that provides protection against myocardial ischemia-reperfusion injury via the activation of P2Y13 receptor and the NO-sGC pathway in RBCs and cardiac PKG. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Swedish Heart and Lung Foundation; Swedish Research Council